Evaluation of Metarhizium brunneum- and Metarhizium-Derived VOCs as Dual-Active Biostimulants and Pest Repellents in a Wireworm-Infested Potato Field - James Bull (Journal of Fungi, 2023)
Wireworm, the larval stages of click beetles, are a serious pest of tubers, brassicas and other important commercial crops throughout the northern hemisphere. No effective control agent has been developed specifically for them, and many of the pesticides marketed as having secondary application against them have been withdrawn from EU and Asian markets. Metarhizium brunneum, an effective entomopathogenic fungus, and its derived volatile metabolites are known to be effective plant biostimulants and plant protectants, although field efficacy has yet to be validated. Field validation of a combined M. brunneum and derived VOC treatments was conducted in Wales, UK, to assess the effects of each as a wireworm control agent and biostimulant. Plots were treated with Tri-Soil (Trichoderma atroviridae), M. brunneum, 1-octen-3-ol or 3-octanone, or combinations thereof. Treatments were applied subsurface during potato seeding (n = 52), and potatoes were harvested at the end of the growing season. Each potato was weighed individually and scored for levels of wireworm damage. Applications of both the VOCs and the M. brunneum individually were found to significantly decrease wireworm burden (p < 0.001). Combinations of M. brunneum and 3-octanone were also found to significantly decrease wireworm damage (p < 0.001), while no effect on yield was reported, resulting in an increased saleable mass over controls (p < 0.001). Herein, we present a novel ‘stimulate and deter’ wireworm control strategy that can be used to significantly enhance saleable potato yields and control wireworm populations, even under high pest pressure densities.